Development of Transcatheter Aortic Valve Implantation and its Clinical Implications (Rhythmos, 2012)
In the early 1990s the concept of transcatheter aortic valve implantation (TAVI) appeared challenging and totally unrealistic. It was a true “resurrection” for Cribier and his whole team performing the first TAVI in an inoperable patient in 2002, using a transeptal antegrade approach and balloon-expandable aortic valve prosthesis. Since then TAVI has been performed in more than 50000 patients worldwide. TAVI is currently indicated in patients with severe symptomatic aortic stenosis (AS) and acceptable life expectancy who are not suitable for aortic valve replacement (AVR) (indication class IB) or as an alternative to aortic valve replacement (AVR) in selected high-risk operable patients (class IIB), according to the “Heart Team” assessment.  The TAVI Heart Team comprised of clinical cardiologists, interventionalists, surgeons, anaesthetists and imaging specialists with expertise in the treatment of valve disease, selects patients suitable for TAVI taking into account advantages and disadvantages of both AVR and TAVI. A logistic EuroSCORE ≥20% (logistic EuroSCORE I tends to overestimate observed mortality risk by a factor of 2 to 3 and a newly updated logistic EuroSCORE II is currently available in clinical practice) or a Society of Thoracic Surgeons (STS) score >10% are suggested as indications for TAVI therapy. Recent publications have identified a number of baseline variables independently associated with mortality or poor outcome in patients undergoing TAVI (low body mass, functional status, left ventricular dysfunction, NT-proBNP, prior stroke, diabetes, chronic kidney disease, anemia, severe tricuspid and mitral regurgitation, porcelain aorta or history of chest radiation) which could be integrated into new scoring systems to quantify and predict the prognosis of TAVI both in the immediate and in the long term... (excerpt)
Keywords: aortic stenosis; transcatheter aortic valve implantion